Primera parte del Parnaso Antartico, de obras amatorias con las 21 epistolas de Ovidio, i el in Ibin, en tercetos - Ovidius Naso, Publius; Mejía, Diego; Rodríguez Gamarra, Alonso (1608)
Sevilla, por Alonso Rodríguez Gamarra, 1608. Language note: Translated version. Citation confidence: An exemplar has been referenced in a major analytical bibliography, or inspected book in hand, by a member of the Iberian Books project team or a collaborating institution. Citation/reference: IB: 51462